NEW TYPE OF ELASTIC ROTATIONAL WAVES IN GEO-MEDIUM AND VORTEX GEODYNAMICS - Alexander V. Vikulin (Геодинамика и тектонофизика, 2015)
Natural-science concepts of rotational movements and the ‘lumpy’ structure of medium are reviewed with a focus on key aspects. Through using torsional traps for hunting and «implementing» mechanical torque for ignition, Homo sapiens developed to man. Vortex movements «impregnated» in spiral structures of shells and torsional movements of toothy whales and fish were intuitively perceived by man as major stable movements of the environment. Based on the above, the ancient philosophy established the concept of the uniform world represented by atomic («noncuttable») structure of medium and vortex movements of ether. Based on conclusive arguments stated by R. Dekart, H. Helmgolz, Lord Kelvin and others within the framework of classical physics and in the first half of the 20th century by scientists in quantum physics and cosmogony, both «quantum structure» («lumpiness») and rotation («vorticity») are integral features of matter – space – time throughout the whole range from elementary particles to galaxies and galactic clusters.Nowadays researchers in natural sciences, particularly in the Earth sciences, call attention again to the problem of structure of matter and its movements. In the 1920s, Chinese geologist Li Siguang established fundamentals of vortex geodynamics. In the second half of the 20th century, Li Siguan’s concepts were developed by geologists O.I. Slenzak and I.V. Melekestsev. Geologist A.V. Peive, mechanic L.I. Sedov and physicist M.A. Sadovsky put forward a concept of block structure of the geo-medium (geological and geophysical medium) and proposed a justified assumption that such blocks can move by own torque. This method of movement is confirmed by results of geological and tectonophysical studies, as well as instrumental geophysical measurements obtained from a variety of stations and focal zones of strong earthquakes. Many researchers, including W. Elsasser and V.N. Nikolaevsky, develop fundamentals of nonlinear wave mechanics of the geo-medium, admitting rotational movements of blocks. According to М.V. Stovas, V.Е. Khain and other researchers, rotation of the planet around its axis is of critical importance for understating the origin of geodynamic movements.Based on the review of results from the previous comprehensive geological and geophysical studies, a conclusion is made on the torque origin of rotating block geo-medium which is termed as Peive–Sedov–Sadovsky medium. Analyses of migration of earthquake foci and volcanic eruptions and movements of edges of tectonic plates provided grounds to design a principally new model, and this rotational model is described in the present publication. Blocks and plates interacting with each other in the model are interrelated by long-range elastic fields which comprise a uniform planetary geodynamic medium, i.e. ‘self-consistent’ state of the geo-medium. Briefly reviewed are data about vortex geological structures and rotary motions of blocks and plates; such data have been detected and recorded in abundance in a variety of geophysical fields. It is stressed that similar, in principle, vortex movements / flows are solutions of the well known Dirichlet–Dedekind–Riemann problem of rotating and gravitating liquid drop that is the problem of the Earth’s equilibrium shape. According to the proposed rotational model, geodynamic solutions of the rotational model combine geodynamic flows in the solution of the problem of the Earth’s equilibrium shape and geologic-geophysical vortex structures and movements on the Earth’s surface in one and the same class of phenomena. It is proposed to apply such solutions for establishing a new geological paradigm – new torque (and/or wave / vortex) geodynamics.